Descriptive analysis of adverse events following immunization with oral cholera vaccine in Lebanon - Abeer Zeitoun; Aya Ibrahim; Sarah Reda El Sayed; Eva Hobeika; Rita Karam; Rita Karam; Rita Karam (Frontiers Media S.A., 2024)
BackgroundA national Oral Cholera Vaccine (OCV) Euvichol-Plus® campaign was launched in Lebanon, in response to the first outbreak in three decades, recorded in October 2022. The OCV vaccination campaign was carried out between November 2022 and February 2023. This study aims to cover adverse events reports, received at the Lebanese National Pharmacovigilance Program's (LNPVP) passive surveillance system.MethodsCase reports were extracted from the LNPVP's database. SPSS software was used to perform statistical analysis, with categorical variables compared using Pearson's χ2 test. A descriptive analysis was performed based on age, gender, vaccine administered, and adverse event(s) associated with the administered vaccine.ResultsA total of 115 Adverse Events Following Immunization (AEFIs) were reported, which corresponded to 46 case reports. The top three reported AEFIs were fever (39.13%), diarrhea (30.43%), and vomiting (30.43%). Reported cases were non-serious (82.6%). The highest proportion of Individual Case Safety Reports (ICSRs) received is attributed to females (56.5%), and the age category of 2 and 11 years old (41.3%). Reporters' age range was 1-74 years old.ConclusionMonitoring AEFIs through the cholera outbreak's emergency campaign favors the safety profile of OCV.